Variação genética de uma população cativa de Mutum-do- Sudeste (Crax blumenbachii Spix, 1825) (Aves: Cracidae) como subsídio para manejo e conservação - Diegues, Savana (Universidade Federal de São Carlos, 2011)
The biodiversity conservation is necessary for the natural ecosystems maintenance and their ecological interactions. The loss of species by human actions, which has been accentuated over the last decades, must be minimized and the search for its conservation is necessary. The endangered species of fauna require efforts for a proper management and the maintenance of genetic diversity is essential to the management success. The Cracid birds are an important group to the maintenance and regeneration of the ecosystems where they live. Thus, support studies to analyze the genetic diversity of these animals are critical for an appropriate management in captivity and wild life. Microsatellites are molecular markers for genetic diversity analyzes widely used and they have advantages over other methods, however, they are specific and they need to be isolated for each species in research. Therefore, microsatellites were prospected to Crax blumenbachii, an endangered type of cracid, validating them and supplying researches for their genetic diversity in search of biodiversity conservation. These markers have been used to analyze the genetic variation and the kinship degree of a captivity population of southeastern curassows from Poços de Caldas/MG breeding site. The results show a number of alleles per locus from two to four, the expected heterozygosity ranged from 0.35 to 0.70 and the observed one ranged from 0.41 to 1.0, which do not have a significant difference. Based on the found PIC values none locus is considered uninformative. The PID, considering all the loci, was 2.46 x 10-7 which means that the loci, characterized together, present a good resolution to individual identification. All the polymorphic loci were in Hardy-Weinberg equilibrium and it was not found significant linkage disequilibrium among any loci pair. It was found no evidence of a recent population bottleneck. The FIS results do not indicate neither excess nor heterozygote deficit at the analyzed loci, implying that the captive management and breeding are being planned properly. With the obtained data from the kinship analyzes it was possible proposing not related couples to reproduction which would maximize the captive population s genetic variability. The developed molecular markers in this research proved to be a good tool for genetic variation assessing of the captive population of the studied species and they supply genetic researches to maximize the management efficiency for cracid birds conservation.
Keywords: Conservação da natureza; Cracídeos; Genética de aves; Parentesco; Microssatélites; Conservação da biodiversidade; Manejo em cativeiro; Cracid birds; Biodiversity conservation; Kinship; Microsatellites; Management in captivity; CIENCIAS BIOLOGICAS::ECOLOGIA